Lake shores dry as dust - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In the past 38 years, Lake Chad has shrunk by 95%. A gradual decline in rainfall since the 1960s and increased water use, especially for irrigation, has led to the decrease. The 1980s marked the construction of internationally financed irrigation...